The Sorcerer's Burden The Ethnographic Saga of a Global Family - Stoller, Paul.; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book emerges from the author's 35 years of research and thought about the Songhay people of Niger. This ethnographic novel follows the life of Omar Dia, the oldest son of a West African sorcerer. When his father falls ill and dies, the great sorcerer vomits a small metal chain onto his chest. Following the path of his ancestors, Omar swallows the chain, becoming his father's successor, which means that he takes on the sorcerer's burden. The book also describes how custodians of traditional knowledge are creatively adapting to the forces of globalization-all in a highly accessible narrative text. .
Part One: Paris, 2000 -- Part Two: Tillaberi, Niger 2000-2001 -- Part Three: Niger/Paris 2001 -- Epilogue. .
Keywords: Ethnology; Ethnography; Fiction